2020
DOI: 10.1177/0308518x20960740
|View full text |Cite
|
Sign up to set email alerts
|

Reluctant financialisaton: Financialisaton without financialised subjectivities in Hungary and the United States

Abstract: The Foucauldian literature on the ‘financialisation of everyday life’ has documented the way neoliberal discourses and practices call forth willing entrepreneurial-investorial and debtor financialised subjects. However, recent qualitative studies on the lived experiences of financialisation suggested that financialised households are often unwilling to adopt the subjectivities of neoliberal discourse (which we call ‘reluctant financialisation’) and only selectively draw on their elements (referred to as ‘varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…As a result, calculative investors develop 'a good cross-section of shares, property, pensions, insurances' (IP32_HI_60). Echoing previous findings (Hillig, 2019b;Pellandini-Simanyi and Banai, 2020), property investment should not be seen here as deviating from investorial concerns but forms part of a financialised subjectivity. Tackling the distrust in financial institutions with the help of further diversifying the asset portfolio aligns with the governmental discourse of individual responsibility.…”
Section: The Calculative Investorsupporting
confidence: 61%
See 1 more Smart Citation
“…As a result, calculative investors develop 'a good cross-section of shares, property, pensions, insurances' (IP32_HI_60). Echoing previous findings (Hillig, 2019b;Pellandini-Simanyi and Banai, 2020), property investment should not be seen here as deviating from investorial concerns but forms part of a financialised subjectivity. Tackling the distrust in financial institutions with the help of further diversifying the asset portfolio aligns with the governmental discourse of individual responsibility.…”
Section: The Calculative Investorsupporting
confidence: 61%
“…Integrating one's own rationalities in the form of emotions, moralities and temporalities is argued to lead to selectively draw on one of the two components of the investor subject. Individuals reject investing in financial assets but perform pervasive calculations when conducting alternative investments (Lai, 2017) or they accumulate financial assets but have not internalised finance rationality (Pellandini-Simanyi and Banai, 2020). What these insights into 'variegated outcomes of financialisation' (Lai, 2017: 915) highlight is that contrary to viewing resistance as solely opposing, it is a rather fluid concept with various facets.…”
Section: 'Activity Of Conducting': the Everyday Investormentioning
confidence: 99%
“…In fact, processes of financial subject formation constitute practical accomplishments that are always in the making. This advances our understanding of everyday financialisation as processes that can generate not only the adoption of ideal financialised subject positions but also variegated forms of contestation and resistance (Fields, 2017; Pellandini-Simányi and Banai, 2020). Moreover, I have shown that a grounded exploration of the remittance-financial inclusion nexus reveals fundamental limits of ‘development’ projects that attempt to expand the possibilities of financial profits in postcolonial economies where everyday incomes are fragile and precarious, and remittances often not sufficient or regular enough.…”
Section: Discussionmentioning
confidence: 99%
“…This finding furthers our understanding of financial subjectivities that characterise everyday financialisation. Rather than pushing remittance recipients to engage in financialised subject positions usually attached to neoliberal discourses and programmes -as 'risk takers', 'self-disciplined investors', 'entrepreneurs' or even 'traders' (Finlayson, 2009;French and Kneale, 2009;Langley, 2006;Thrift, 2008) -financialisation initiatives face serious limitations and can lead to variegated subjectivities of contestation (Fields, 2017;Pellandini-Sima´nyi and Banai, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We build on these key findings from feminist political economy to examine everyday financialisation from a gender perspective. Literature on everyday financialisation portrays it as a variable and contested process, in particular through the theorisation of variegated financial subjectivities, meaning the way that logics and practices of finance are entwined with other everyday rationalities (Lai 2016, Pellandini-Simányi and Banai 2021, Agunsoye 2021). However, this body work rarely takes account of gender as an important dynamic of lived experience, foregrounding the need to better understand how gender shapes the ways in which individuals respond to and interact with financialised systems (Roberts 2015, Fine 2017, Best et al 2021.…”
Section: Introductionmentioning
confidence: 99%